Structure and practices in hospitals of the Apice ON Project: a baseline study - Yluska Myrna Meneses Brandão e Mendes; Daphne Rattner (Universidade de São Paulo, 2020)
ABSTRACT OBJECTIVE To describe some characteristics of the 97 teaching hospitals participating in the Projeto de Aprimoramento e Inovação no Cuidado e Ensino em Obstetrícia e Neonatologia (Apice ON-Project for Improvement and Innovation in Care and Teaching in Obstetrics and Neonatology). METHODS The semester prior to the beginning of the program was adopted as the baseline to evaluate the subsequent structural and processes changes of this project. Secondary data from the first half of 2017 were extracted from the National Registry of Health Establishments (NRHE), the Hospital Information System and the Sistema de Informações sobre Nascidos Vivos (SINASC-Live Birth Information System). RESULTS Before the implementation of the project, only 66% of the hospitals had a Baby-friendly Hospital Initiative, only 3% offered special accommodations for high-risk pregnant women, mothers and their newborns, and 45.4% hospitals adopted the skin-to-skin contact; 97% hospitals had separate rooms for pre-labor and vaginal delivery (93%), not following the recommendations of the Ministry of Health; nine hospitals (9%) had no rooming-in; there were few obstetrics nurses (less than 1% of professionals enrolled in the NRHE), and in only six hospitals the proportion of births assisted by this professional was above 50% of vaginal deliveries, while in eight this percentage ranged between 15% and 50%; the average cesarean section rate was 42%, ranging between 37.6% (Southeast) and 49.1% (Northeast); ten hospitals did not charge for companions according to inpatient hospital authorization. CONCLUSION The study strengthens the relevance of the Apice ON project as an inducer of change of the care model in teaching hospitals and, therefore, as a strategy for the implementation of the national public policy represented by the Stork Network.